Răspuns :
|-----------|
|-----------|--------| +1
|--------------------|--------|+1
|-----------------------------|---------|+1
69-3=63
63:3=31
31+1=32
|-----------|--------| +1
|--------------------|--------|+1
|-----------------------------|---------|+1
69-3=63
63:3=31
31+1=32
|---------------|
|---------------|----| + 1
|--------------------|----| + 1
|-------------------------|----| + 1
intai facem 69 - 3 pentru ca sunt trei nr. si este egal cu 66
dupa facem 63 : 3 = 21
31 +1 = 32
Sper ca te-am ajutat!